Determination of Dynamic Viscosity of Viscous Oils using Mach Zehnder Digital Holographic Method - Rittirong Nuansri; Pichet Limsuwan; Prathan Buranasiri (My University, 2018)
The digital in-line holography based on Mach Zehnder interferometer (MZDIH) was setup for the determination of dynamic viscosity of the viscous oils. The spherical irons were used as the falling objects in the viscous oils. The hologram images of the iron falling along its entire path were recoded as a video file on the CMOS camera. The recorded hologram images were reconstructed on the holoviewer program via MATLAB. Then, the diameter and velocity of the iron were obtained. Finally, the dynamic viscosity of viscous oils were determined and compared with standard values. From the experimental results, it can be concluded that the MZDIH method is the simple and precise tool for determining the dynamic viscosity of fluids.
Keywords: Holographic interferometry; Digital holography; Falling (accident); Viscous liquid; Digital Holography and Microscopy